A systematic review of the use of atypical antipsychotics in autism. - Barnard, L; Young, A; Pearson, J; Geddes, J; O'Brien, G (2002)
Conventional antipsychotic medication is commonly prescribed to patients with autistic spectrum disorder. However, a high incidence of severe adverse reactions highlights the need to find more favourable treatments. Atypical antipsychotics may combine efficacy in ameliorating some autistic symptoms with a lower incidence of some adverse reactions. This article reviews the use of atypical antipsychotics in autistic disorder, with particular focus on behaviour, cognition and physical well-being. Thirteen studies using risperidone, three using olanzapine, one using clozapine, one using amisulpride and one using quetiapine were identified. Few firm conclusions can be drawn due to the limitations of the studies; however, there is an indication that risperidone may be effective in reducing hyperactivity, aggression and repetitive behaviours, often without inducing severe adverse reactions. Olanzapine and clozapine may also be effective; however, there is little evidence for using amisulpride or quetiapine in this population. Randomized trials are required to clarify the effectiveness of these agents.